Implementation of Zonasi-Based Barus Student Admission Management on the Effectiveness of Student Distribution in Palopo City High School - Diana Diana; Rustan Santaria; Fatmarida Sabani; Kaharuddin Kaharuddin; Nurdin Kaso (Journal of Indonesian Islamic Studies, 2022)
This study aims to: (1) determine the implementation of management functions in the acceptance of new students based on zonation in Palopo City. (2) determine the effectiveness of the distribution of new students based on zonation in Palopo City. (3) find the supporting and inhibiting factors for the application of zoning-based new student admissions. This research use desciptive qualitative approach. The research was conducted at SMA Negeri 6 Palopo, SMA Negeri 1 Palopo and SMA Negeri 2 Palopo. There are two research subjects, namely the primary subject consisting of the Principal, Deputy Principal for Student Affairs and the PPDB Committee and the secondary subject, namely the results of documentation. Techniques and data collection instruments used were observation, interviews and documentation. Test the validity of the data through the triangulation process. The results of the study show that (1) the implementation of management functions in the Zoning-based PPDB, namely the first planning stage which includes the implementation of a follow-up to the issuance of a decree from the head of the South Sulawesi education office regarding PPDB in 2020/2021 by carrying out a School Principal Working Meeting which discusses the study. Regarding the admission route for new students, the division and determination of zonation for each school and preparation for the formation of an implementing committee and carrying out PPDB preparations in the form of supporting facilities and infrastructure as well as human resources in the form of operators. Second, organizing the formation and stipulation of the implementing committee as well as the zoning determination through a decree of the South Sulawesi provincial education office. The three stages of implementation include the socialization process, announcement of the acceptance schedule, implementation of registration, and determination of selection results. The four stages of evaluation include evaluations carried out at the school scope by improving services and evaluations carried out at the South Sulawesi provincial education office by making improvements to the PPDB application. (2) The implementation of zoning-based PPDB management is effective in the distribution process of students at SMA Palopo City as evidenced by more than 50% of new students being accepted into each Education Unit, namely SMA Negeri 6 Palopo, SMA Negeri 1 Palopo and SMA Negeri 2 Palopo. (3) The supporting factors for the successful implementation of zoning-based PPDB are adequate facilities and infrastructure, efficiency in the socialization process using social media, adequate school human resources and internet network access that is almost evenly distributed in Palopo City. The inhibiting factors are that there are still prospective students who are constrained in accessing technology, registering outside the zoning, areas far from the nearest school, some areas that do not have internet network access, and server capacity that is still lacking.